(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this work, several different drying methods were used to organize deep processing of grape residues collected at grape processing plants using waste-free technology. The initial moisture content of grape cake is 49,36 ± 3,45%. Grape cake composition is considered a good raw material for the production of biofuel products of the second generation. During the experiment, the drying efficiency of a vacuum dryer, conventional drying and drying in the open sun were studied.